Westrom Von Honorius bis Justinian - Börm, Henning (W. Kohlhammer GmbH, 2013)
The West of the Roman Empire experienced a chain of dramatic events and development from 396 AD onwards. The last Western emperor was deposed in 476 AD and Justinian abolished the Western Roman court in 554 AD. These events, which mark the transition from antiquity to the Middle Ages in Europe, are often explained by a "civic migration". However, this book, by contrast, highlights internal Roman conflicts: Western Rome was not conquered. Its successive empires only superseded the authority of the imperial government, when endless civil wars had led to the collapse of Roman rule. A systematic overview of Empire, administration, army, economy and religion completes the presentation. Der Westen des Imperium Romanum erlebte ab 395 n. Chr. eine Kette von dramatischen Ereignissen und Entwicklungen. 476 wurde der letzte Westkaiser abgesetzt, 554 schaffte Justinian auch den weströmischen Hof ab. Diese Vorgänge, die für Europa den Übergang von der Antike zum Mittelalter markieren, sind oft durch eine "Völkerwanderung" erklärt worden. Der vorliegende Band rückt dagegen innerrömische Konflikte ins Zentrum: Westrom wurde nicht erobert. Seine Nachfolgereiche traten erst an die Stelle der kaiserlichen Regierung, als endlose Bürgerkriege zum Kollaps der römischen Herrschaft geführt hatten. Ein systematischer Überblick über Kaisertum, Verwaltung, Armee, Wirtschaft und Religion rundet die Darstellung ab